Women’s demand for late-term abortion – A social or psychiatric issue? - Nikolić, Gordana; Samardžić, Ljiljana; Krstić, Miroslav (Vojnosanitetski pregled, 2014)
Introduction/Aim. Induced termination of unwanted pregnancy after 12th gestational week (late-term abortion) is legally restricted in Serbia as well as in many other countries. On the other hand, unwanted pregnancy very often brings women into the state of personal crisis. Psychiatric indications for legally approved late-term abortion on women’s demand include only severe psychiatric disorders. The aim of this paper was to compare sociodemographic, psychological characteristics and claimed reasons for abortion in the two groups of women with late-term demand for abortion – the group of women satisfying legally prescribed mental health indications, and the group of women not satisfying these indications. The aim of the study was also to determine predictive validity of the abovementioned parameters for late-term abortion as the outcome of unwanted pregnancy. Methods. A total of 62 pregnant women with demand for late-term abortion were divided into two groups according to the criteria of satisfying or not satisfying legally proposed psychiatric indications for late-term abortion after psychiatric evaluation. For the assessment of socio-demographic and psychological parameters sociodemographic questionnaire and symptom checklist – 90 revised (SCL-90®) scale were used, respectively. The outcome of unwanted pregnancy was followed 6 months after the initial assessment. Results. The obtained results showed a statistically significant difference between the groups in educational level, satisfaction with financial situation, elevated anxiety and distress reactions. Unfavorable social circumstances were the main reason for an abortion in both groups and were predictive for an abortion. A 6-month follow-up showed that women had abortion despite legal restrictions. Conclusion. Pregnant women with psychiatric indication for late-term abortion belong to lower socioeconomic and educational level group compared to women without this indication who have more frequently elevated anxiety and distress reactions to unwanted pregnancy. It is necessary to have more accurate guidelines for mental health indications for legally approved late-term abortion, respecting social circumstances. Preventive measures are of great importance in order to lower the risk of illegally performed late-term abortions.